Dystrybucja tkanki tłuszczowej wśród studentów o jednakowej wysokości ciała = Distribution of adipose tissue among the students of the same body height - Tatarczuk, Józef; Asienkiewicz, Ryszard; Malinowski, Andrzej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this article is to present the distribution of adipose tissue in the groups of women and men of the same body height.
Keywords: somatic features; dimorphism; academic youth; comparative characteristics; cechy somatyczne; dymorfizm; młodzież akademicka; cechy porównawcze